Yang-warming method in the treatment of diabetic peripheral neuropathy: an updated systematic review and meta-analysis - Sharad Panthi; Xirun Jing; Chenghan Gao; Tianshu Gao (BMC, 2017)
Abstract Background Various studies have suggested the effectiveness of Chinese medicine in the treatment of diabetic peripheral neuropathy (DPN). There are several principles and methods in Chinese medicine for the treatment of DPN and yang-warming method is one of them. The purpose of this meta-analysis was to review the effectiveness and safety of yang-warming method using yang-warming Chinese medicine (YCM) in the treatment of DPN. Methods A computer-based search of the articles from January 2001 to April 2016 with Chinese and English databases such as CNKI, CBM, Wanfang, VIP, Medline, Embase and Cochrane central register of controlled trials as well as manual search of the related articles was conducted. Randomized Controlled Trials (RCTs) comparing yang-warming Chinese medicines with western medicines in the treatment of DPN were considered for the study. The outcome measures were change in the sensory or motor nerve conduction velocity, total efficacy rate evaluated by clinical symptoms improvement, and adverse events. Two authors independently assessed the methodological quality of the included articles using Jadad scale and the twelve criteria recommended by Cochrane Back Review Group. Data were analyzed using RevMan 5.3 software provided by Cochrane collaboration. Results A total of 25 articles were taken for the study. Meta-analysis results showed that yang-warming Chinese medicines used in the formula alone or in combination with western medicines improved the nerve conduction velocity (NCV) in comparison to western medicines alone (p < 0.001). There was also a significant difference in the total efficacy rate between the two groups (p < 0.001). Most of the included studies did not clearly report the adverse events. Conclusions Yang-warming Chinese medicines alone or in combination with western medicines were apparently better than conventional western medicines in the treatment of DPN. Because of the poor quality of the reported works that were available for the present meta-analysis, it is earlier to claim the superiority of yang-warming method using YCM to western medicines for the treatment of DPN. To support these early findings, further standardized and rigorous RCTs are required.